Quality of comprehensive care provided by caregiver-mothers to children under 3 years of age, beneficiaries of Cuna Más National Program, Huánuco - Adriano Huaytán , Yudy (2019)
Objective: To describe the quality of comprehensive care provided by caregiver-mothers for children under 3 years old, beneficiaries of Cuna Más National Program, Huánuco, 2019. Methods: It was a cross-sectional, prospective and observational study, with a descriptive design and a quantitative approach. Sample comprised of 80 caregivers of a total of 100 caregivers of the day care service of Cuna Más National Program, Peru. An interview guide of general characteristics and a scale of care quality were applied, the latter was validated and reliable. The ethical aspects of the research were taken into consideration. A frequency analysis was carried out at the descriptive level. Results: Quality of comprehensive care in its three components. In the child learning dimension, evidenced 70% (56) of high-level quality. In the child health dimension, 71.3% (57) showed a medium level of quality. Finally, in the nutrition and feeding dimension, 27.5% (22) showed low quality of care. Overall, 52.5% (42) evidenced a quality of comprehensive care at a medium level, followed by 33.8% (27) with a high-level quality of care. Conclusion: Quality of comprehensive care for the beneficiary child of the day care service of Cuna Más program, carried out by caregiver-mothers, was medium level. It shows the need to strengthen competencies of comprehensive care for beneficiary children and constant supervision by specialists of care such as nursing professionals.   DOI: https://doi.org/10.31876/sl.v3i2.64